The production of Newcastle disease virus-like particles in Nicotiana benthamiana as potential vaccines - Smith, Tanja; O’Kennedy, Martha M.; Ross, Craig S.; Lewis, Nicola S.; Abolnik, Celia (Frontiers in Plant Science, 2023)
Newcastle disease (ND) is a highly contagious viral respiratory and neurological disease that has a severe impact on poultry production worldwide. In the present study, an expression platform was established for the transient production in N.bethamiana of ND virus-like particles (VLPs) for use as vaccines against ND. The expression of the ND Fusion (F) and/or Hemagglutinin-neuraminidase (HN) proteins of a genotype VII.2 strain formed ND VLPs in planta as visualized under the transmission electron microscope, and HN-containing VLPs agglutinated chicken erythrocytes with hemagglutination (HA) titres of up to 13 log2.The immunogenicity of the partially-purified ND VLPs was confirmed in specific-pathogen-free White leghorn chickens. Birds receiving a single intramuscular immunization with 1024 HA units (10 log2) of the F/HN ND VLPs administered with 20% [v/v] Emulsigen®-P adjuvant, seroconverted after 14 days with F- and HN-specific antibodies at ELISA titres of 5705.17 and HI geometric mean titres (GMTs) of 6.2 log2, respectively. Furthermore, these ND-specific antibodies successfully inhibited viral replication in vitro of two antigenically closely-related ND virus isolates, with virus-neutralization test GMTs of 3.47 and 3.4, respectively. Plant-produced ND VLPs have great potential as antigen-matched vaccines for poultry and other avian species that are highly immunogenic, cost-effective, and facilitate prompt updating to ensure improved protection against emerging ND field viruses.